Spray-assisted deposition of CsPbBr3 films in ambient air for large-area inorganic perovskite solar cells. (December 2018) - Duan, Jialong; Dou, Dawei; Zhao, Yuanyuan; Wang, Yudi; Yang, Xiya; Yuan, Haiwen; He, Benlin; Tang, Qunwei
Abstract: High-purity cesium lead bromide (CsPbBr3 ) perovskite films are expected to promote the commercial manufacture of inorganic perovskite solar cells (PSCs). We present here a spray-assisted deposition of high-quality CsPbBr3 films in ambient air by spin-coating a PbBr2 layer and sequentially spraying CsBr multilayer to simplify the film fabrication technology. Upon optimizing spray deposition at four cycles, a high-purity CsPbBr3 phase is prepared and a maximized power conversion efficiency of 5.68% is achieved for the carbon-based inorganic PSC device. Furthermore, molybdenum disulfide quantum dots with an intermediate energy level are set at CsPbBr3 /carbon interface to markedly increase charge extraction and to suppress electron-hole recombination, arising from the perovskite grain boundary passivation. Finally, the optimal inorganic PSC yields a stabilized efficiency of 6.80% under one sun illumination. Using this spray-assisted deposition method, this CsPbBr3 solar cell with an active area of 1 cm 2 achieves an efficiency of 4.12%. The photovoltaic performances are relatively stable even upon 80% relative humidity over 700 h without encapsulation. Graphical abstract: Highlights: A spray-assisted method has been developed to fabricate CsPbBr3 films. Impurity crystal phase of all-inorganic pervoskite is suppressed. CsPbBr3 solar cell with a device area of 1 cm 2 achieves an efficiency of 4.12%. The optimal device shows excellent long-term stability over 700 h.